Sensing of dangerous DNA. (July 2017) - Gasser, Stephan; Zhang, Wendy Y.L.; Tan, Nikki Yi Jie; Tripathi, Shubhita; Suter, Manuel A.; Chew, Zhi Huan; Khatoo, Muznah; Ngeow, Joanne; Cheung, Florence S.G.
Abstract: The presence of damaged and microbial DNA can pose a threat to the survival of organisms. Cells express various sensors that recognize specific aspects of such potentially dangerous DNA. Recognition of damaged or microbial DNA by sensors induces cellular processes that are important for DNA repair and inflammation. Here, we review recent evidence that the cellular response to DNA damage and microbial DNA are tightly intertwined. We also discuss insights into the parameters that enable DNA sensors to distinguish damaged and microbial DNA from DNA present in healthy cells.